The Application of Open Government in Improving Public Services in Public Service Malls in Indonesia - ., Andriana; Sailan, Manan; Aslinda, Andi; Yamin, Muhammad; ., Wahira; Kasmawati, Andi; Niswaty, Risma (Journal of Ecohumanism, 2025)
This study aims to analyse the implementation of Open Government through Open Assets, Open Engagement, Open Services at the Public Service Mall in Barru Regency. Qualitative research methods were used in the research conducted in Barru Regency. Data was obtained from observations, interviews with various informants and collecting documents for writing needs. After that, the data was analysed independently by the researcher to provide interesting research results and conclusions. This research also used Nvivo 12 Pro software to analyse the research results. The results of this study show that the implementation of Open Government in the Barru Regency Public Service Mall is still ‘quite low’, as seen from the non-optimal implementation of the Open Government framework values. Openness of information, data, transparency of decision-making, and multi-stakeholder cooperation have not been consistently implemented. Every problem is solved at the level of each agency without any partnership or deliberation space. Community involvement in Open Engagement is also minimal, with a lack of participation in providing opinions or formulating solutions together. Employee capacity building is still limited and conducted separately by local government and the private sector. The Open Services aspect is also less than optimal, as mechanisms for accessing public information and data, including service procedures, have not been well socialised. In addition, information related to policies and service fees is still limited, so MPP Digital innovation and service integration are needed to improve transparency and accessibility.